Analysis of the Role of the Human Resources Bureau in Improving Performance at Government Institutions in Indonesia - Desi Aryati Sulastri; Bunga Alamanda Syarifatul Abadiyah; Budi Supriyatno; Azis Hakim (CV. Publikasi Indonesia, 2024)
The problems that will be faced by the HR Bureau, namely the globalization of technology, competence, and human resources and bureaucratic reform, greatly affect the performance of government institutions in Indonesia. This problem must be answered by increasing the role of the HR bureau in carrying out its duties and functions in HR management. Human Resource Management is very fundamental for a government agency, because it is needed and must be managed properly so that it becomes superior and competent HR and has a commitment to the organization. The method used in this research uses descriptive analysis method by collecting data through literature study from various sources. From this research it can be concluded that HR has its own role and duties, and the development of HR quality is needed in global developments, and HR competencies must be improved through the process of education, training, and coaching.